Pengembangan Lembar Kerja Siswa (LKS) Biologi Berbasis Keislaman pada Materi Sistem Reproduksi - Suhaili, Hidayati; Zulyetti, Diana; Hidayat, Opi Rahmah; Dinda, Mutiara (JOEAI (Journal of Education and Instruction), 2022)
This study aims to produce Islamic-based Student Worksheets (LKS) on reproductive system material for class XI students that are valid and practical. This research method uses the development method, using the 4-D (four D) model, define, design, develop, and deploy. Given the limitations of the authors, this study only uses three stages of development, namely the define, design, and develop stages. The results of the study explain the processing of questionnaire validation data, resulting in a percentage of 97.3% belonging to the very valid category. The results of the practicality questionnaire test for teacher responses were 88% in the category of very practical results and 85% of students' responses to practicality were in the very practical category. In conclusion, the worksheets developed have very valid qualities and are very practical for use by teachers and students, so they are suitable for use as learning worksheets in the subject of Islamic Biology Reproductive Systems Keywords: Biology Student Work Institute, Islam, Reproductive System